CAFFEINE AND PERFORMANCE IN ENDURANCE SPORTS: A SYSTEMATIC REVIEW OF THE LITERATURE - Maia Neto, José Dalvo; Ferreira, Heraldo Simões; Assunção Neto, Marcos Vinícius (Seven Editora, 2026)
Introduction: Caffeine is one of the most studied and widely used ergogenic substances by endurance athletes, with consistent evidence of improved physical performance. Objective: To conduct a systematic review of the literature on the effects of caffeine supplementation on the performance of athletes in endurance sports, analyzing dosages, timing of administration, mechanisms of action, and possible adverse effects. Methods: A systematic search was performed in PubMed, Scopus, Web of Science, and SPORTDiscus databases, using the descriptors ’caffeine’, ’endurance’, ’performance’, ’supplementation’, and ’athletes’. Randomized clinical trials published between 2010 and 2024 involving endurance athletes were included. Results: 47 studies met the inclusion criteria. Caffeine supplementation (3-6 mg/kg) significantly improved performance in endurance events (p<0.05), with an average increase of 2-4% in time to exhaustion and a 1-3% reduction in race time. Mechanisms include adenosine receptor antagonism, increased fatty acid mobilization, reduced perception of effort, and improved muscle contractility. Adverse effects were reported at doses above 9 mg/kg. Conclusion: Caffeine is an effective and safe ergogenic aid for endurance athletes when used at doses of 3-6 mg/kg, administered 45-60 minutes before exercise. Future studies should investigate individual variability in caffeine response and supplementation periodization strategies. DOI: https://doi.org/10.56238/sevened2025.036-157